The potential of rice field resulting from conversion of sago (Metroxylon spp) land at toboso village West Halmahera regency - Ramli Hadun (Jurnal Agrivet, 2012)
The research aims to examine the potential of a land for the development of lowland rice crop, to analyze land cultivation system to support the growth and production of rice crop. Physical examination on land is conducted using survey method with rigid grid observation distance. Economical aspects related to the examined farm are: (1) farm profit, (2) R/C ratio analysis, and (3) Break Even Point (BEP) analysis. Research result shows that the actual potential of the rice field resulting from conversion of sago land has low nutrient (N total, available P2O5, and K2O) availability. Result from rice farm analysis shows that the average area is 2.700 m2 , with average production is 699 kg or 0,26 kg m-2 or equal to 2.586,30 kg Ha -1 . The average net income is Rp. 2,660,333,-. The farm is feasible to be developed with R/C ratio value of 4,72. Rice farming with area of 2.700 m2 will break even if the income gained by farmer is Rp. 315.928 per season, production of 52,93 kg per season, or sold result of Rp. 1.482 kg -1 on area of 204,66 m2 .Keywords: Land potential, land evaluation, farm analysis